Zika Virus and Microcephaly in Health District 13D02 of Ecuador (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of the investigation was to determine the repercussions generated by the Zika virus in District 13D02 in Ecuador and to explain the protocol follow-up applied to children born with microcephaly. The province of Manabí was one of the most affected by the epidemiological behavior of the Zika virus in the country, showing pregnant women as a vulnerable population, which, as a result of the virus, generated a proliferation of birth defects, such as the case of microcephaly, addressed the study of these cases, located in the cantons of Manta and Montecristi. For this purpose, a descriptive methodology was used based on a documentary analysis model, obtaining as results that in District 13D02 were identified during 2017, a total of 45 pregnant women carrying the Zika virus, the same who received a protocol follow-up that involved home visits, ultrasounds, and prenatal control. In the follow-up of the cases, the patient in the so-called "Case of Cuba" did not present any symptoms that would attract attention, registering a head circumference of 39 cm and a degree of disability of 33%. Regarding another case, called the “Colorado Case,” the minor was diagnosed with West G40 Syndrome, congenital dislocation of the Q65 hip, and congenital M21 clubfoot, currently registering a 36-cm head circumference and 46% disability. It could also be determined that these minors are not part of effective inclusion programs that provide them with care according to their special needs.